A new blood fluke,Parasanguinicola vastispina gen. nov., sp. nov. (Trematoda: Sanguinicolidae), from sea bass Lates calcarifer (Centropomidae) cultured in Malaysia - Herbert, B.W.; Shaharom, F.M. (Springer-Verlag, 1995)
A new sanguinicolid blood fluke, Parasanguinicola vastispina, is described from sea bass Lates calcarifer cultured in Malaysia. It is distinguished by its massive armature and widely spaced genital pores, the female pore being pre-ovarian. P. vastispina inhabits the branchial arteries, dorsal aorta, mesenteric venules and renal artery of its host. No pathological effect was observed in infected fish. © 1995 Springer-Verlag.